2015
DOI: 10.18235/0000142
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity Growth in Latin America and the Caribbean and Other World Regions: An Analysis of Climatic Effects, Convergence and Catch-up

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…The TE estimates reported here are relatively low when compared to the available evidence for Latin America (Bravo‐Ureta et al ., ; Lachaud et al ., ). However, it is important to keep in mind that POSAF‐II was implemented in areas that were severely damaged by Hurricane Mitch in October 1998.…”
Section: Resultsmentioning
confidence: 97%
“…The TE estimates reported here are relatively low when compared to the available evidence for Latin America (Bravo‐Ureta et al ., ; Lachaud et al ., ). However, it is important to keep in mind that POSAF‐II was implemented in areas that were severely damaged by Hurricane Mitch in October 1998.…”
Section: Resultsmentioning
confidence: 97%
“…TFP is composed of technical change and technical efficiency, where technical change refers to "a change in the production technology that can come from improved methods of using the existing inputs or through changes in input quality", and technical efficiency refers to the "ratio of the actual output to the maximum potential output" (Kumbhakar, Wang and Horncastle, 2015). 6 See Lachaud, Bravo-Ureta and Ludeña (2015) for an analysis of effects of climate variability on TFP growth, and projections of the impacts of climate on estimates of Climate Adjusted Total Factor Productivity (CATFP) in LAC.…”
Section: Introductionmentioning
confidence: 99%
“…So, in order to support the analysis, Lachaud et al (2015) has analyzed agricultural productivity growth in LACs, covering the period 1961-2012. This research has included climate variables in the study for a better understanding of agricultural performance in the region.…”
Section: Introductionmentioning
confidence: 99%
“…They have proved that 6 countries fulfill the efficiency measures: Argentina, Belize, Bolivia, Brazil, Costa Rica and Mexico present the best agricultural performance. Lastly, Lachaud et al (2015) and Moreno-Moreno et al (2017) have concluded that new technology in agriculture will increase the ability to reduce pollution in agriculture but also achieve better agricultural performance.…”
Section: Introductionmentioning
confidence: 99%